Leader–follower dynamics during early social interactions matter for infant word learning - Goupil, Louise; Dautriche, Isabelle; Denman, Katherine; Henry, Zion; Marriott-Haresign, Ira; Wass, Sam (Proceedings of the National Academy of Sciences - PNAS, 2024)
We know little about the mechanisms through which leader–follower dynamics during dyadic play shape infants’ language acquisition. We hypothesized that infants’ decisions to visually explore a specific object signal focal increases in endogenous attention, and that when caregivers respond to these proactive behaviors by naming the object it boosts infants’ word learning. To examine this, we invited caregivers and their 14-mo-old infants to play with novel objects, before testing infants’ retention of the novel object-label mappings. Meanwhile, their electroencephalograms were recorded. Results showed that infants’ proactive looks toward an object during play associated with greater neural signatures of endogenous attention. Furthermore, when caregivers named objects during these episodes, infants showed greater word learning, but only when caregivers also joined their focus of attention. Our findings support the idea that infants’ proactive visual explorations guide their acquisition of a lexicon.